Back to the Origin? Popular Sovereignty from French Revolution to Current Anti-Corruption Movements: the Spanish Case in Historical Perspective - Caruso, Loris (PARTECIPAZIONE E CONFLITTO, 2018)
Analyses of the Spanish mobilization cycle between 2011 and 2013 concur with considering the critiques of corruption (and the growing discredit of traditional parties), one of the two key factors that has been determining in the emergence of the 15-M movement (the Indignados), the other being the economic crisis. This article investigates the link between anti-corruption from below and the claim for popular sovereignty in the Spanish case. In Spain movements’ requests and discourses have found a clear translation on the electoral plan. Podemos, a party founded in 2014, considers itself the electoral expression of 15-M. For these reasons, the analysis focuses on Podemos and its anti-corruption discourse as well. The analysis is conducted in a historical perspective. Popular sovereignty has been the fundamental claim of the first social movements born in Europe in the second half of the eighteenth century. A historical comparison is carried out between the anti-corruption frames of democratic movements between 1760 and 1848 and the present ones, giving particular attention to their nexus with the claim for popular sovereignty.